2020
DOI: 10.1590/1678-6971/eramg200043
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Influence of the Conspicuous Consumption of Fast Fashion on Identity Construction on Instagram

Abstract: Purpose: The objective of this investigation is to analyze the influence of the conspicuous consumption of fast fashion products on Instagram on the identity construction process of female fashion consumers. Originality/value: Filling a gap in the literature relating to conspicuous consumption and identity construction, this investigation analyzes the consumption dynamics, investigating relevant phenomena on a current and relevant online social network: Instagram; and explaining, in an analysis by categories,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(39 reference statements)
0
3
0
1
Order By: Relevance
“…People portraying a higher level of consumption pattern show higher desire and intention to buy fashion cause-related marketing products. Satisfaction resulting from conspicuous consumption and possession of certain goods drives FF consumption (Dantas and Abreu, 2020). Furthermore, previous research has shown that conspicuous consumption is a strong determinant of purchase intention (Jain, 2019;Huang and Wang (2018).…”
Section: Conspicuous Consumption and Fast Fashion Purchase Intentionmentioning
confidence: 94%
See 2 more Smart Citations
“…People portraying a higher level of consumption pattern show higher desire and intention to buy fashion cause-related marketing products. Satisfaction resulting from conspicuous consumption and possession of certain goods drives FF consumption (Dantas and Abreu, 2020). Furthermore, previous research has shown that conspicuous consumption is a strong determinant of purchase intention (Jain, 2019;Huang and Wang (2018).…”
Section: Conspicuous Consumption and Fast Fashion Purchase Intentionmentioning
confidence: 94%
“…Conspicuous consumption is claimed to boost one's reputation in society and can be accomplished by public displays that signify and convey wealth to others. It even requires spending just to inflate the ego along with ostentatious show of riches coupled with ostentatious display of wealth (Veblen, 1899(Veblen, , 1965Mason, 1981;O'cass and McEwen, 2004; SBR 18,4 Dantas and Abreu, 2020;Aw et al, 2021). Conspicuous spending is a technique for people to demonstrate their financial power, but that is not confined to wealthy elite.…”
Section: Conspicuous Consumption and Fast Fashion Purchase Intentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Essas curtidas validam sua popularidade e status entre seus pares, ademais ter um grande número de seguidores também evidencia a popularidade de um indivíduo (Sheldon & Bryant, 2016). Essa busca por popularidade Andressa Hennig Silva, Mikaela Daiane Prestes Floriano pode envolver os consumidores em comportamentos de consumo conspícuo, a fim de buscarem a aprovação contínua dos pares (Dantas & Abreu, 2020). Assim sendo, propõe-se a última hipótese deste estudo.…”
Section: Andressa Hennig Silva Mikaela Daiane Prestes Florianounclassified